2022
DOI: 10.1177/02601060221093430
|View full text |Cite
|
Sign up to set email alerts
|

Does the 2019 Canada’s Food Guide meet the needs of young athletes?

Abstract: Background: The Canada’s Food Guide (CFG) encourages Canadians to consume a balanced plate. However, this recommendation may not meet the nutritional needs of young athletes who have increased nutritional requirements. Aim: To evaluate how the 2019 CGF can be used to meet the nutritional needs of young athletes. Method: Five menu scenarios were created using the CFG’s balanced plate and recipes from Health Canada. Each menu was analyzed to compare nutrient and energy needs of an index athlete (15-year-old male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…A recent study has revealed that there may be eating disorders especially in adolescent athletes and that the nutritional information of the athletes was insufficient (Magee et al, 2023). For example, in a study, it was seen that the dietary guidelines applied for the nutrition of adolescent athletes in Canada had positive effects on athletes (Heidl et al, 2022). Also adolescent athletes need more energy than their non-athlete peers (Desbrow, 2014) and may feel more fatigue than adult athletes (Bergeron et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has revealed that there may be eating disorders especially in adolescent athletes and that the nutritional information of the athletes was insufficient (Magee et al, 2023). For example, in a study, it was seen that the dietary guidelines applied for the nutrition of adolescent athletes in Canada had positive effects on athletes (Heidl et al, 2022). Also adolescent athletes need more energy than their non-athlete peers (Desbrow, 2014) and may feel more fatigue than adult athletes (Bergeron et al, 2015).…”
Section: Introductionmentioning
confidence: 99%